2021
DOI: 10.1002/msc.1536
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of knee osteoarthritis: A review of current evidence and clinical guidelines

Abstract: Background: Knee osteoarthritis (OA) is one of the most common and debilitating degenerative joint diseases worldwide. While radiography is the most commonly used imaging modality, it is associated with drawbacks which newer modalities such as magnetic resonance imaging (MRI) and ultrasound could overcome. Nevertheless, the role of imaging in clinical practice and research in knee OA has not been clearly defined. Furthermore, guidelines on imaging in knee OA from different authoritative bodies have not been co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 91 publications
0
18
0
1
Order By: Relevance
“…Previous systematic reviews of OA guidelines focussed on management or focussed on specific joint (Kinds et al, 2011;Lee et al, 2021;Pencharz et al, 2001;Zhang et al, 2007). A recent review on the role of imaging in knee OA searched PubMed for published clinical guidelines, which only identified four guidelines (Lee et al, 2021). The current study included an extensive search of six bibliographic databases, four health improvement and guideline databases as well as a hand search of nine professional organisations' websites for guidelines across all OA sites except the spine and temporomandibular joint.…”
Section: Relationship Between Guideline Publication and Trend In X-ra...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous systematic reviews of OA guidelines focussed on management or focussed on specific joint (Kinds et al, 2011;Lee et al, 2021;Pencharz et al, 2001;Zhang et al, 2007). A recent review on the role of imaging in knee OA searched PubMed for published clinical guidelines, which only identified four guidelines (Lee et al, 2021). The current study included an extensive search of six bibliographic databases, four health improvement and guideline databases as well as a hand search of nine professional organisations' websites for guidelines across all OA sites except the spine and temporomandibular joint.…”
Section: Relationship Between Guideline Publication and Trend In X-ra...mentioning
confidence: 99%
“…Previous systematic reviews of OA guidelines focussed on management or focussed on specific joint (Kinds et al, 2011;Lee et al, 2021;Pencharz et al, 2001;Zhang et al, 2007). A recent review on the role of imaging in knee OA searched PubMed for published clinical guidelines, which only identified four guidelines (Lee et al, 2021).…”
Section: Relationship Between Guideline Publication and Trend In X-ra...mentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis that occur at the PF joint, patellofemoral osteoarthritis (PFOA), is highly prevalent and clinically important yet still under-investigated [3]. For instance, there are clear diagnostic guidelines for tibiofemoral (TF) joint OA ( [4,5,6,7]). Often these guidelines involve the use of well-validated radiographic grading systems for evaluating the severity of TFOA, such as Kellgren and Lawrence (KL) grading system [8] and Osteoarthritis Research Society International (OARSI) standardized atlas [4].…”
Section: Introductionmentioning
confidence: 99%
“…MRI is a key modality for clinical and research assessments of Musculoskeletal (MSK) injuries and OA, and can be used to assess morphological (through assessment of cartilage thickness) and microenvironment composition changes (through the use of relaxometry, eg, T 1 rho and T 2 mapping) due to natural aging and injury. [2][3][4][5] MRI-derived morphological changes in physically active adolescents have been studied, e.g., a study reporting that the most frequent knee injury is Wilberg patella type 2 in males and type 3 in females. 6 Another study conducted on children and adolescents with acute patellar dislocation showed a high incidence of osteochondral injury in the aftermath of the dislocation.…”
mentioning
confidence: 99%